Medijsko-politični paralelizem - Pajnik, Mojca (Dve domovini, 2017)
The article starts with the thesis that metaprocesses of mediatisation define the operation of the media to the degree that "media logic" follows political agendas. We verify the thesis based on a qualitative analysis of journalistic commentary (editorials) that were published in the Slovenian daily newspaper Delo (August-December 2015) on the topic of European migration policy (quota system, Schengen regime, bilateral agreements etc.). The analysis shows that migration policy is legitimized by commentary that omits the views of non-governmental sources and is largely based on Eurocentric imaginings of Europe.
Keywords: Begunci; Časniki; Delo (periodična publikacija); Migracijska politika; Migration policy; Newspapers; Poročanje; Refugees; Reporting